Challenges and perceptions of e-learning for educational sustainability in the “new normality era” - Melinda Timea Fülöp; Teodora Odett Breaz; Ioan Dan Topor; Constantin Aurelian Ionescu; Larisa-Loredana Dragolea (Frontiers in Psychology, 2023)
BackgroundAll universities were faced with the challenges of e-learning when they suddenly had to switch to distance learning in March 2020 due to COVID-19 regulations. Several challenges may arise when implementing e-learning, including an insufficient budget or problems with adoption. Nevertheless, the role of digitalization is to ensure the university’s long-term sustainability. Indeed, the future of e-learning depends on future generations, which increasingly accept new technologies.ObjectivesThis study aimed to analyze the factors that stimulate university students’ acceptance of technology.MethodologyThe study population comprised Romanian university students who took online courses during the COVID-19 pandemic. A questionnaire survey was employed to gather primary data. The surveys were distributed between January and February 2022. In particular, 1,875 questionnaires were received from students, who were the focus of this study (the results for teachers were presented in previous research). To process and interpret the data, the method of modeling with structural equations (SEM) was used. The data collected were processed using SPSS and AMOS.FindingsThe results indicate that external factors do not influence perceived usefulness. Accordingly, students consider that the perceived ease of use does not influence the behavior intention to use new technologies.ConclusionThe results linked e-learning satisfaction to academic success and Romanian students who utilized e-learning during the pandemic. In addition, the results indicate that external factors do not influence perceived usefulness. Accordingly, students consider that the perceived ease of use does not influence the behavior intention to use new technologies. The results validated the basic variables of the TAM model.ImplicationsThe study presents a series of theoretical, practical, and societal implications that can guide universities in adopting sustainable development goals.